Fixation Location and Stability in Best Vitelliform Macular Dystrophy - Lorenzo Bianco, MD; Alessandro Arrigo, MD, PhD; Alessandro Marchese, MD; Alessio Antropoli, MD; Emanuela Aragona, MD, PhD; Lamberto La Franca, MD; Luca Mauro, MD; Adelaide Pina, MsC; Rashid Hassan Farah, MsC; Giulia Basile, MsC; Francesco Bandello, MD, FEBO; Maurizio Battaglia Parodi, MD (Ophthalmology Science, 2023)
Purpose: To analyze fixation location and stability in best vitelliform macular dystrophy (BVMD) and test their association with best-corrected visual acuity (BCVA). Design: Observational, cross-sectional study. Participants: Thirty patients (55 eyes) affected by genetically confirmed BVMD were followed up at the Retinal Heredodystrophies Unit of IRCCS San Raffaele Scientific Institute, Milan. Methods: Patients underwent testing with macular integrity assessment (MAIA) microperimeter. Fixation location was measured as distance in degrees (°) between preferred retinal locus (PRL) and estimated fovea location (EFL); fixation was defined as eccentric when the distance between PRL and EFL exceeded 2°. Fixation stability was graded as stable, relatively unstable, or unstable and expressed as bivariate contour ellipse area (BCEA, °2). Main Outcome Measures: Fixation location and stability. Results: The median distance of the PRL from the anatomic fovea was 0.7°, and fixation location was eccentric in 27% of eyes. Fixation was graded as stable in 64% of eyes, relatively unstable in 13%, and unstable in 24%, with a median 95% BCEA of 6.2°2. The atrophic/fibrotic stage was associated with worse fixation parameters (all P < 0.01). Both PRL eccentricity and fixation stability were linearly associated with BCVA: every 1° increase in PRL eccentricity was associated with a 0.07 logarithm of the minimum angle of resolution (logMAR) worse BCVA (P < 0.0001) while every 1°2 increase in 95% BCEA was associated with a 0.01 logMAR worse BCVA (P < 0.001). No significant intereye correlation was found for PRL eccentricity and fixation stability, as well as no association between the patient's age and fixation parameters. Conclusions: We demonstrated that most eyes affected by BVMD retain a central stable fixation and provided evidence that both fixation eccentricity and stability are strongly associated with visual acuity in BVMD. These parameters may serve as secondary end points for future clinical trials. Financial Disclosure(s): Proprietary or commercial disclosure may be found after the references.